Features of preparation of teachers of technology: retrospective analysis - Драшко, Олена (Pedagogy of Higher and Secondary Education, 2015)
Drashko E .N. Features of preparation of teachers of technology: retrospective analysis. The article deals with the experience of labour preparation teachers in Ukraine and in Republic of Poland. Attention is concentrated on the system of preparation of future teachers technologists (labour preparation, attendant labour) and its separate components.